AN ANALYSIS THE PROJECT BACKGROUND FACTORS IN CONSTRUCTION PROJECTS - Pensalwar, Shalaka; Charpe, P.S.; Shiral, Ranjit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Construction is a driver of every economy, including India. It uses a lot of people, material, and machinery, and it has a deadline. Consequently, it helps the country’s economy improve tremendously. A technical breakthrough has had a significant impact on the building sector. Some Indian industries are using quality management systems. Particularly among construction firms capable of managing megaprojects, quality management systems have been extensively used and embraced. Because of the inherent challenges of the construction business, there is currently no reliable method for objectively gauging the system’s efficacy in this field. The objectives are to evaluate the Project Background Aspect or factors in construction projects.